ANALISIS HUBUNGAN KARAKTER DISIPLIN DENGAN KARAKTER TANGGUNG JAWAB BELAJAR SISWA KELAS XI DAN XII SMA NEGERI 1 LIRIK KABUPATEN INDRAGIRI HULU - Afrianti, Ririn; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted in SMA Negeri 1 Lirik Indragiri Hulu. The background of this study was the lack of responsibility of student in learning, lack of willingness of students to record the lessons, less concerned about whether he brought a textbook or not, available or not stationery, and less prepare materials needed to support the understanding of new materials which will be studied, indifferent to the teacher's explanations, not serious when asking/giving opinion, do homework carelessly, do not attempt to complete the task in optimal capability. The purpose of this study was to determine the relationship of the Disciplinary Character to Responsibility Character of Student Class XI and XII SMA Negeri I Lirik Indragiri Hulu District. The population of this study were all students of class XI and XII, total 207 students and the study sample was 25% of the total population of as many as 51 students. Data were analyzed using questionnaire and interview which kind of quantitative descriptive analysis using product moment correlation equation. The results showed that there was a relation between Discipline Character and the Student Responsibility Character of Class XI and XII SMA Negeri I Lirik Indragiri Hulu. This was proven by significant testing, with results of robserve (0.588)> rtable (0.273) or Ha accepted. Equation product moment correlation r xy = 0.588, which means the relation Responsibility Discipline Student Class XI and XII SMA Negeri I Lyrics Indragiri Hulu is sufficient. With the achievement of the value of the variable X at 75.49%, which was in the High category, and the value of the variable Y by 70.44%, which was the High category.Keywords: Character Discipline, Responsibility Character